The Role of Artificial Intelligence in Enhancing Risks in Media Marketing Campaigns in Saudi Arabian Marketing Companies (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study explores the Role of Artificial Intelligence in Enhancing Risks in Media Marketing Campaigns in Saudi Arabian Marketing Companies. AI enhances marketing practices by improving audience targeting, analyzing large datasets to extract patterns and trends, and providing personalized content. However, it also poses significant challenges, including privacy issues, ethical concerns, and the risk of bias in algorithms. The study aims to identify the applications of AI in digital marketing, evaluate its impact on competitive advantages, and explore the risks associated with its use. It also recommends the effective and ethical implementation of AI technologies in marketing strategies. The research methodology involves data collection through surveys and previous studies, followed by statistical and qualitative data analysis. The findings indicate a high awareness and positive perception of AI's potential to improve marketing strategies and manage risks. However, they also highlight the need for strict data privacy policies and employee training on ethical AI use. The study concludes that AI can significantly enhance marketing effectiveness and security if used responsibly and with appropriate measures to mitigate risks.
Keywords: Artificial Intelligence; Digital Marketing; Risk Management